1999
DOI: 10.1177/016264349901400202
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Special Education Program Home Pages

Abstract: The World Wide Web (WWW) is a universal medium that has revolutionized the dissemination and gathering of information; however, on-line barriers limit the accessibility of the WWW for individuals with disabilities. Federal legislation directs that the provision of assistive technology devices and services enable individuals with disabilities to benefit from the opportunities available to their neighbors and peers without disabilities. The purposes of this study were to evaluate the accessibility of university … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
0
24
1
Order By: Relevance
“…These results demonstrate that evaluating the homepage alone is not sufficient when evaluating web pages for accessibility. Previous studies using only the homepage in the analysis (Davis, 2002;Flowers et al, 1999;Lazar et al, 2003;Lazar and Greenidge, 2006;Loiacono and McCoy, 2006;Klein et al, 2003;Paris, 2006;Spindler, 2002;Yu, 2002) may not have shown the whole picture of accessibility. However, the WAB scores for levels 1, 2, and 3 of these web sites are highly correlated and previous Homepage not enough studies that included more pages than just the homepage (Diaper and Worman, 2003;Sloan et al, 2002;Thompson, 2003), if even a limited number of deeper pages (Jackson-Sanborn et al, 2002;Hackett et al, 2004), may have provided better estimates of the accessibility of the web sites under evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…These results demonstrate that evaluating the homepage alone is not sufficient when evaluating web pages for accessibility. Previous studies using only the homepage in the analysis (Davis, 2002;Flowers et al, 1999;Lazar et al, 2003;Lazar and Greenidge, 2006;Loiacono and McCoy, 2006;Klein et al, 2003;Paris, 2006;Spindler, 2002;Yu, 2002) may not have shown the whole picture of accessibility. However, the WAB scores for levels 1, 2, and 3 of these web sites are highly correlated and previous Homepage not enough studies that included more pages than just the homepage (Diaper and Worman, 2003;Sloan et al, 2002;Thompson, 2003), if even a limited number of deeper pages (Jackson-Sanborn et al, 2002;Hackett et al, 2004), may have provided better estimates of the accessibility of the web sites under evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research on Web accessibility in educational settings found that 30-60% of university Web sites met basic requirements for Web accessibility (Flowers, Bray, & Algozzine, 1999;Krach, 2007;Zaphiris & Ellis, 2001), and 16-25% of elementary school as well as 42% of K-12 district Web sites were accessible (Bray, Flowers, & Gibson, 2003;Bray, Flowers, Smith, & Algozzine, 2003). Therefore, expectations were that the current findings for K-12 Web sites would be similar.…”
Section: Discussionmentioning
confidence: 63%
“…Widely used in accessibility studies, Bobby is a testing tool that identifies and prioritizes Web site accessibility problems (Watchfire, 2002). Significant studies employing Bobby include Chilson (2002), Flowers et al (1999;, Graves (2001), Romano (2002), Stein (2002), Stowers (2002), and West (2000;. Such wide level of acceptance provides a basis for comparing the results of the current study with previous research.…”
Section: Accessibility Evaluation Toolmentioning
confidence: 87%
“…In their study of community college Web sites, Flowers, Bray, and Algozzine (2001) found that only 23% of the sites evaluated were accessible to individuals with disabilities. Flowers, Bray, and Algozzine (1999) also studied special education home pages and found that 73% of these had accessibility problems, and that 71% of the errors were severe. In her study of federal Web sites, Stowers (2002) found that only 13.5% of the sites evaluated met the basic standards for accessibility, despite the fact that the study was performed well past the Section 508 implementation deadline.…”
Section: Introductionmentioning
confidence: 99%